Citizen journalism as conceptual practice : postcolonial archives and embodied political acts of new media - Blaagaard, Bolette (Frontiers of the political, 2018)
Provides a conceptualisation of citizen journalism as a political practice developed through analyses of an historical and postcolonial case.